Frugal Innovation for Inclusive and Sustainable Development in Africa - (:unkn) unknown (My University, 2024)
Frugal innovation has emerged as a promising approach to addressing the unique challenges and resource constraints African communities face. This article presents a comprehensive analysis of the key principles, frameworks, and case studies of frugal innovation in Africa, exploring its transformative potential in driving inclusive development and sustainable progress. Drawing on extensive research and illustrative examples, the article examines the defining characteristics of frugal innovation, such as affordability, functionality, sustainability, and adaptability, which distinguish it from traditional innovation models. The article delves into the theoretical foundations that underpin frugal innovation, including the Jugaad Innovation framework, the Empathic Design approach, the Bottom of the Pyramid (BoP) framework, the Reverse Innovation concept, and the Frugal Innovation framework. These conceptual models provide valuable insights into the drivers, manifestations, and applications of frugal innovation in Africa. Through a detailed examination of sectoral case studies, the article showcases the diverse ways in which frugal innovations are addressing pressing social, economic, and environmental challenges in areas such as healthcare, energy, agriculture, water, and sanitation. These case studies illustrate the ingenuity, resourcefulness, and community-driven nature of frugal innovation, highlighting its potential to create affordable, accessible, and adaptable solutions that empower marginalized populations. The article further explores the barriers and enablers of frugal innovation, drawing on the insights of prominent African scholars, such as Mvemba Phezo Dizolele and Carlos Lopes. It examines critical issues, including policy and regulatory frameworks, financing mechanisms, innovation ecosystem development, and capacity-building efforts. It outlines strategies for fostering enabling environments that nurture the growth and scaling of frugal innova
Keywords: African Research